2016
DOI: 10.1246/cl.160769
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Superconcentrated Aqueous Electrolyte to Improve the Electrochemical Performance of Calcium-ion Batteries

Abstract: Herein, we applied a novel superconcentrated aqueous electrolyte in calcium-ion batteries for the first time to improve electrochemical performance by decreasing the hydration number and radius of calcium ions. Their charge/discharge capacities with the superconcentrated electrolyte were ca. 13% higher than that with the dilute electrolyte. The cycling performance improved quite remarkably in the superconcentrated electrolyte, because of the suppression of structural collapse of copper hexacyanoferrate used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 27 publications
2
57
1
2
Order By: Relevance
“…Recently, some works demonstrated that the existence of water can effectively facilitate the Ca 2+ ion diffusion because of the weakened charge density derived from the shielding effect of water, which is similar to Mg‐ion battery mentioned above. Jeong and Lee investigated the effect of electrolyte concentration on the storage performance of Ca 2+ ion in CuHCF host. They found that the superconcentrated aqueous electrolyte, 8.37 mol L −1 Ca(NO 3 ) 2 , is beneficial to the improvement of discharge capacity and cycle life compared to dilute electrolyte (1 mol L −1 Ca(NO 3 ) 2 ).…”
Section: Aqueous Batteries Using Multivalent Ions (Zn2+ Mg2+ Ca2+ mentioning
confidence: 99%
“…Recently, some works demonstrated that the existence of water can effectively facilitate the Ca 2+ ion diffusion because of the weakened charge density derived from the shielding effect of water, which is similar to Mg‐ion battery mentioned above. Jeong and Lee investigated the effect of electrolyte concentration on the storage performance of Ca 2+ ion in CuHCF host. They found that the superconcentrated aqueous electrolyte, 8.37 mol L −1 Ca(NO 3 ) 2 , is beneficial to the improvement of discharge capacity and cycle life compared to dilute electrolyte (1 mol L −1 Ca(NO 3 ) 2 ).…”
Section: Aqueous Batteries Using Multivalent Ions (Zn2+ Mg2+ Ca2+ mentioning
confidence: 99%
“…Bulk water has an electrochemical stability window of about 1.23 V. Recently, however, reports of high‐voltage aqueous batteries (2.5 to 4 V) have claimed the successful use of interfacial controls to isolate bulk water from electrochemical contact ,,. This was achieved through the creation of an artificial solid–electrolyte interface (SEI) on the electrode surface, which passivates against proton/hydroxyl electrolytic decomposition, but allows cation‐specific diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…5a and 5b, improved cycling performance is observed in the concentrated electrolyte. In our previous study, it was demonstrated that the crystalline lattice structure of an electrode could be maintained after cycling if the hydration number of the cations were decreased, leading to improved cycling performance [22]. Therefore, in this study, the reason for the improved cycling performance in the concentrated electrolyte may be the decreased hydration number of the zinc ions.…”
Section: Resultsmentioning
confidence: 76%
“…In our previous study, it was demonstrated that a PBA electrode with a collapsed crystalline structure realizes relatively poor electrochemical performances in an aqueous electrolyte [22]. As indicated by the XRD results, the crystallinity of ZnHCF synthesized using 0.1 mol dm -3 Zn(NO 3 ) 2 is to that of ZnHCF synthesized using 0.05 mol dm -3 Zn(NO 3 ) 2 , which likely accounts for the differences in the charge/discharge properties of the two ZnHCF electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation